Marketing of Handloom Products: A Case Study of Thenzawl Cluster in Mizoram - Ramswamy, Rama; Jyoti Kumar, N. V. R. (Indian Journal of Marketing, 2012)
In India, the handloom enterprises are largely household-based and an important provider of rural non-farm employment. This paper is based on the mapping of Thenzawl, a village in Mizoram, which has developed as a handloom cluster. Most of the entrepreneurs in the cluster are tribal women who have chosen to be entrepreneurs in their own right, notwithstanding the number of looms owned by them. The paper has analyzed some important aspects of marketing of the micro artisan enterprises in terms of share of different products in total sales, channels of distribution, terms of payment for sales, sales promotion techniques, and extent of participation of sample enterprises in exhibitions and fairs. The researchers have offered suggestions for improving the marketing practices of the enterprises through cluster intervention initiatives to enable the cluster to sustain and grow.